Effect of a School-Delivered “Tobacco-Free Home” Campaign on Adolescent Smoking and Periodontal Risk: An Analysis of Psychosocial Pathways - I Wayan Agus Wirya Pratama; Gusti Ayu Yohanna Lily; I Gusti Agung Ayu Chandra Iswari Dewi; Jithesh Jain (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Adolescent smoking contributes to early-onset periodontal disease, while institutional prevention programs often lack reinforcement at home. This study evaluated an 8-week psychosocial intervention integrating school-based Cognitive Behavioral Therapy (CBT) with a family-engaged Tobacco-Free Home (TFH) campaign to improve smoking behavior, risk attitudes, and social support. Materials and Methods: A quasi-experimental non-equivalent control group design involved 259 adolescent smokers in Bali, Indonesia. Intact classrooms were clustered into intervention (n = 139) and control (n = 120) groups. Psychosocial variables were measured at baseline and week 8. Data were analyzed using t-tests, Pearson correlation, and ANCOVA adjusted for baseline covariates. Result and Discussion: The intervention group showed significantly greater improvements in all outcomes compared with controls. Smoking behavior improved significantly (Δ = 0.76, p < 0.001), while ANCOVA confirmed strong group effects (F = 62.14). Positive correlations (r > 0.49) indicated that smoke-free home norms reinforced cognitive self-regulation, supporting social support as a key mediator. Conclusion: The CBT–TFH model effectively modified determinants of adolescent smoking behavior, with social support as an important catalyst for change. By extending intervention effects into the home environment, this strategy may help reduce long-term periodontal disease risk.